2007
DOI: 10.1104/pp.107.100537
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and Not Embolism Is Required for Wound-Induced Tylose Development in Stems of Grapevines

Abstract: The pruning of actively growing grapevines (Vitis vinifera) resulted in xylem vessel embolisms and a stimulation of tylose formation in the vessels below the pruning wound. Pruning was also followed by a 10-fold increase in the concentration of ethylene at the cut surface. When the pruning cut was made under water and maintained in water, embolisms were prevented, but there was no reduction in the formation of tyloses or the accumulation of ethylene. Treatment of the stems with inhibitors of ethylene biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 52 publications
1
70
0
Order By: Relevance
“…Even though a high concentration of sugars occurred in LBSN berries, generally they are not suitable for making wine, nevertheless such clusters can be harvested and used for making wines of different style depending upon its timing of inception. Although LBSN damages phloem tissues [17,95], this study revealed that the xylem vessels developed tyloses possibly in a way similar to pruned grapevine stems that develop tyloses induced by biosynthesis of ethylene [99]. The extent of development and amount of obstruction caused by tyloses determines the formation of necrotic area [100].…”
Section: Lbsn and Ebsnmentioning
confidence: 99%
“…Even though a high concentration of sugars occurred in LBSN berries, generally they are not suitable for making wine, nevertheless such clusters can be harvested and used for making wines of different style depending upon its timing of inception. Although LBSN damages phloem tissues [17,95], this study revealed that the xylem vessels developed tyloses possibly in a way similar to pruned grapevine stems that develop tyloses induced by biosynthesis of ethylene [99]. The extent of development and amount of obstruction caused by tyloses determines the formation of necrotic area [100].…”
Section: Lbsn and Ebsnmentioning
confidence: 99%
“…PD symptom development in grapevines depends on the interactions between the pathogen and the host vine's xylem tissue, through which the pathogen may achieve its systemic spread (Purcell and Hopkins, 1996;Pérez-Donoso et al, 2010;Sun et al, 2011). Since the path for this spread is the host's xylem system, xylem tissue and its vessels have become the major focus for studying potential X. fastidiosa-host vine interactions at the cellular or tissue levels (Fry and Milholland, 1990b;Stevenson et al, 2004a;Sun et al, 2006Sun et al, , 2007Thorne et al, 2006).…”
mentioning
confidence: 99%
“…One major aspect is to clarify the process of tylose development itself, in which an open vessel may be gradually sealed (Sun et al, 2006(Sun et al, , 2008. Our investigations of the initiation of tylose formation in grapevines have identified ethylene as an important factor (Pérez-Donoso et al, 2007;Sun et al, 2007). In terms of the relationship of tyloses to grapevine PD, studies have so far led to several controversial viewpoints that are discussed below (Mollenhauer and Hopkins, 1976;Fry and Milholland, 1990b;Stevenson et al, 2004a;.…”
mentioning
confidence: 99%
“…water-or air-filled) at the time of freezing (Canny, 1997;Melcher et al, 2003;Cobb et al, 2007;Mayr et al, 2007;Johnson et al, 2012). Both transverse (Hukin et al, 2005;Sun et al, 2007;Johnson et al, 2012) and longitudinal (Utsumi et al, 1999) cryo-SEM sections have been prepared, but only provide a snapshot of a single point in time and in a single, two-dimensional plane. Similarly, NMR imaging was used in several studies as a nondestructive visualization tool to study the functional status of the xylem in vivo (Holbrook et al, 2001;Clearwater and Clark, 2003).…”
mentioning
confidence: 99%